Transgenerational Effect of Different Collard Green Genotypes On Plutella xylostella (Lepidoptera: Plutellidae) - Marques Pinheiro, Aline [UNESP] (2024)
The adverse effects of intensive synthetic insecticide use present the challenge of finding pest-resistant cultivars in economically important plants. Since intrinsic characteristics of cultivars can influence the population dynamics of specialist insects, this study evaluated the fitness of the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), on different genotypes of collard green (Brassica oleraceae var. acephala L.) using fertility life table parameters. Neonate larvae were reared to adulthood feeding daily on leaves from each collard green genotype. Adults originating from larvae fed on leaves from genotype 8 H had shorter lifespans compared to those fed on other genotypes. The shortest oviposition period was observed in 14 N (3.37 days), while the longest was observed in 1 A (10.10 days). Lower oviposition rates were observed on 8 H (38.3 eggs/female), 14 N (42.7 eggs/female), and 9 I (44.5 eggs/female) compared to 1 A (228.0 eggs/female). Moths reared on genotypes 8 H and 1 A exhibited the lowest (7.02 offspring per individual) and highest (69.0 offspring per individual) net reproductive rate (R0), respectively. The lowest intrinsic rate of increase (rm) were obtained when larvae fed on genotypes 8 H (0.05 days−1) and 14 N (0.07 days−1). These results suggest that intrinsic characteristics of B. oleraceae can impact the longevity and reproductive potential of P. xylostella. Specifically, genotypes 32 GUA, 2 B, and HS resulted in low adult emergence, while 8 H, 9 I, 14 N, and HI CROP genotypes negatively affected the performance of this pest.